Morphological spectrum of renal cell carcinoma, unclassified: an analysis of 136 cases. Issue 2 (24th October 2017) - Perrino, Carmen M; Grignon, David J; Williamson, Sean R; Idrees, Muhammad T; Eble, John N; Cheng, Liang
Abstract : Aims: Renal cell carcinoma, unclassified (RCCU) is a category that includes a morphologically and biologically heterogeneous group of tumours that are unable to be diagnosed as other well‐defined entities. We aim to describe the morphological findings of tumours within this category and to determine the most frequent morphological features leading to classification difficulty. Methods and results: One hundred and thirty‐six cases of RCCU were examined. Patients ranged in age from 23 to 87 years. Seventy‐seven patients were men and 59 were women. International Society of Urological Pathology (ISUP) grade was most commonly 3 ( n  = 66), followed by 2 ( n  = 42) and 4 ( n  = 28). Tumour size ranged from 0.6 to 24.9 cm. The American Joint Committee on Cancer (AJCC) pathological T categories included pT1a ( n  = 50), pT1b ( n  = 14), pT2a ( n  = 7), pT2b ( n  = 4), pT3a ( n  = 50) and pT4 ( n  = 9). Forty‐four cases included lymph node(s), 41% of which ( n  = 18) had metastases. Tumours were assessed for a variety of histological features and assigned to the following morphological groups: predominantly oncocytoma/chromophobe RCC‐like; clear cell RCC‐like; papillary RCC‐like; collecting duct‐like; and pure sarcomatoid differentiation. The majority of the oncocytoma/chromophobe and clear cell RCC‐like phenotypes were low stage (pT1 or pT2). The papillary RCC‐like, collecting duct‐like and pure sarcomatoid phenotypes were mainly high stage (pT3 or pT4). Conclusions: Renal cell carcinoma, unclassified is a term that encompasses tumours with a variety of morphological features and a wide biological spectrum. The most common source of diagnostic difficulty was tumours composed of predominantly eosinophilic cells.